2017
DOI: 10.1021/acs.biochem.7b00885
|View full text |Cite
|
Sign up to set email alerts
|

Internal Motions of Basic Side Chains of the Antennapedia Homeodomain in the Free and DNA-Bound States

Abstract: Basic side chains play crucial roles in protein-DNA interactions. In this study, using NMR spectroscopy, we investigated the dynamics of Arg and Lys side chains of the fruit fly Antennapedia homeodomain in the free state and in the complex with target DNA. We measured 15N relaxation for Arg and Lys side chains at two magnetic fields, from which generalized order parameters for the cationic groups were determined. Mobility of the R5 side chain, which makes hydrogen bonds with a thymine base in the DNA minor gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…One underlying theme to all of the mechanisms reported above is the conformational malleability of DBDs. The co-evolved but frustrated landscape of DBDs can thus manifest as complex binding thermodynamics ( 37–40 ), anomalous heat capacity profiles ( 41 ), downhill-like folding mechanistic behaviors ( 14 ) and large dynamics even in the DNA-bound form ( 42 , 43 ). An extreme case is that of a DBD folding upon binding to DNA (or vice versa), while it remains disordered in the absence of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…One underlying theme to all of the mechanisms reported above is the conformational malleability of DBDs. The co-evolved but frustrated landscape of DBDs can thus manifest as complex binding thermodynamics ( 37–40 ), anomalous heat capacity profiles ( 41 ), downhill-like folding mechanistic behaviors ( 14 ) and large dynamics even in the DNA-bound form ( 42 , 43 ). An extreme case is that of a DBD folding upon binding to DNA (or vice versa), while it remains disordered in the absence of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…In the crystal structure of the same complex, there are 9 ion pairs of phosphates and basic side chains with an interionic O···N distance being <6 Å. Additionally, one of the three basic side chains in the disordered tail, which is not resolved in the crystal structure, is known to interact with DNA. 59 Thus, the diffusion-based method can accurately determine the number of cations released upon protein–nucleic acid association. This method will be useful particularly for systems involving disordered interfaces that electrostatically interact with DNA or RNA.…”
Section: Counterion Release Upon Protein–nucleic Acid Associationmentioning
confidence: 99%
“…Solution NMR studies of Arg and Lys side chains at the protein–DNA/RNA interfaces showed that basic side chains interacting with phosphate groups are generally more mobile than basic side chains interacting with nucleotide bases. 12 , 59 , 64 68 This difference in mobility may be related to steric restriction and other interactions in the grooves compared with those with the phosphate. More importantly, however, the dynamic equilibria between the CIP state and the solvent-separated ion pair (SIP) enhance the mobility of basic side chains forming ion pairs with phosphates ( Figure 4 A).…”
Section: Dynamics Of Macromolecular Ion Pairsmentioning
confidence: 99%
“…In particular, Iwahara and co-workers have shown that the heteronuclear in-phase single quantum coherence experiment (HISQC) is more sensitive at detecting side chain amine signals because of its ability to reduce the relaxation effect of hydrogen exchange on 15 N atoms [ 54 ]. The Iwahara group also developed much of the theory behind the relaxation of 15 N atoms in -NH 3 + groups and showed that DNA binding to a protein changes dynamics of some of its lysine and arginine residues [ 55 , 56 ]. Their methodology is easily adaptable to GAG-binding proteins.…”
Section: Characterizing Lysine and Arginine Residues In Gag-bindinmentioning
confidence: 99%
“…Methods also exist to look at the relaxation of the 15 N atom in lysine side chain amine groups. They have been productively applied to the study of DNA-binding proteins [ 55 , 56 ]. Although there is currently no report of application of these methods to GAG-binding proteins, the utilization of these methods on GAG-binding proteins should shed important insights into protein-GAG interactions.…”
Section: Probing Gag-induced Changes In Protein Dynamics and Oligomentioning
confidence: 99%